A ratiometric two-photon probe for Ca2+ in live tissues and its application to spinal cord injury model. (October 2017) - Kim, Hyung Joong; Lim, Chang Su; Lee, Hyo Won; Lee, Hye Sue; Um, Yun Ju; Kumar, Hemant; Han, Inbo; Kim, Hwan Myung
Abstract: Ratiometric imaging with a small-molecule probe is important for the in-situ quantitative analysis of chemical events. We developed a ratiometric two-photon fluorescent probe (SCa1-I REF ) derived from dual dyes with different Stokes shifts. This probe has two identical windows: a Ca 2+ -sensing window and an internal reference window, with eliminated FRET interference.SCa1-I REF shows a marked change in the ratio upon response with Ca 2+, significant two-photon brightness, considerable selectivity for Ca 2+, and cell loading ability with low cytotoxicity. The ratiometric two-photon microscopy images revealed that this probe could directly and quantitatively estimate Ca 2+ in live neurons and various tissues including rat spinal cord tissue. The studies of spinal cord injury model revealed that the Ca 2+ level was significantly affected by elapsed time after injury. These results will provide useful applications for in-situ [Ca 2+ ]i imaging and for the development of effective ratiometric probes.